2017
DOI: 10.1002/pat.4236
|View full text |Cite
|
Sign up to set email alerts
|

Design of electrospun polyacrylonitrile nanofiber–coated nonwoven structure for sound absorption

Abstract: Acoustic felts are commonly used in white goods. Bearing that into mind, this paper aims to enhance sound absorption behavior of such felts, in particular, within the low and medium frequency ranges. In doing so, wool and jute felt samples were coated with electrospun polyacrylonitrile nanofibrous membrane. These nanocoated felts were studied in terms of their sound absorption performance, air permeability, and surface morphology. The results indicated that the air permeability of the felts could be drasticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…By using a magnetic stirrer for 24 h under laboratory conditions (20 ± 2°C and 65 ± 2% relative humidity), a polymer solution with a concentration of 15% w/w was obtained. PAN polymer was selected since it has been shown that it works well as sound absorber [3336]. Moreover, they are less affected by ambient relative humidity and temperature (Tg: 95°C) changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a magnetic stirrer for 24 h under laboratory conditions (20 ± 2°C and 65 ± 2% relative humidity), a polymer solution with a concentration of 15% w/w was obtained. PAN polymer was selected since it has been shown that it works well as sound absorber [3336]. Moreover, they are less affected by ambient relative humidity and temperature (Tg: 95°C) changes.…”
Section: Methodsmentioning
confidence: 99%
“…Nanofibers can be manufactured by electrospinning which have so many applications [32]. Accordingly, nanofibers have recently been investigated by many researchers for acoustic applications [33–37]. It was shown that good sound absorption properties can be achieved by adding polyacrylonitrile (PAN) nanofiber to the polyurethane foam structure.…”
Section: Introductionmentioning
confidence: 99%
“…This material is trending in textile-based research where different researchers are working to manufacture smart textiles to generate energy [ 22 23 ]. Nanofibers have many technical applications such as in air and liquid filtration [ 24 25 ], tissue engineering [ 26 – 27 ], drug delivery [ 28 ], wound dressings [ 29 ], sound adsorption [ 30 ], cosmetics [ 31 ], and sensor devices [ 32 34 ]. In filtration processes, electrospun nanofibers can be employed for removing volatile organic compounds (VOCs) from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…To heighten the acoustic properties of fibrous materials, they have been optimized by thermoplastic polymer, [10] component, [11] processing parameters, [12] and nonwoven structure. [13] Ramamoorthy et al fabricated silica aerogels in organic fiber nonwoven fabrics and studied their sound absorption properties. The results exhibited higher sound absorption coefficient (SAC) than the pure nonwoven fabrics in the all frequency ranges.…”
Section: Introductionmentioning
confidence: 99%
“…To heighten the acoustic properties of fibrous materials, they have been optimized by thermoplastic polymer, component, processing parameters, and nonwoven structure . Ramamoorthy et al fabricated silica aerogels in organic fiber nonwoven fabrics and studied their sound absorption properties.…”
Section: Introductionmentioning
confidence: 99%